TEKNIK PENULISAN MODUL KETERAMPILAN BELAJAR UNTUK MAHASISWA - Rina Sukawati, Mita Septiani, Suprayekti, Sridadi Suparto (Perspektif Ilmu Pendidikan, 2014)
To gain the graduate competence successfully, the university students need to have learning skills. Assisting the students to have the learning skills can be done by providing them with an appropriate module. This research was intended to identify the procedure of developing the module and produce the module which the students can use dependently to improve their learning skills. The research was conducted at the School of Education, State University of Jakarta. as from February through April 2013. The data to be analyzed descriptively were collected by studying the relevant documents, observation, and distributing questionairs to the students. The research found out three phases in producing the module: planning, writing preparation, and writing and editing. Besides, the research produced a the module for learning skills.